The effect of transparency and accountability on the prevention of pension fund fraud: a case study of a BUMD in Jawa Barat - Fadhilah, Fadya Noor; Yusuf, Paulus Sugianto (Gema Wiralodra, 2023)
Fraud prevention is all efforts made to deter potential perpetrators, narrow the space for movement, and identify activities that pose a fraud risk. This study examines the effect of transparency and accountability on preventing pension fund fraud. The variables in this study consist of transparency and accountability as independent variables and prevention of pension fund fraud as the dependent variable. The measurement scale used in this study is ordinal. The research method used is a survey method with a quantitative approach. The statistical tests used in this study are validity, reliability, normality test, multicollinearity, heteroscedasticity, coefficient of determination, ttest, and Ftest using the Statistical Product Service Solution (SPSS) application version 26. The results of this study indicate that partial transparency has a significant effect on preventing pension fund fraud, while accountability has no significant effect on preventing pension fund fraud. However, simultaneously transparency